“Dérives du poème”. La poétique dans l’oeuvre de Gaston Bachelard et le travail critique de Claude Esteban (Altre Modernità, 2012)
Drawing on Claude Esteban’s essay “Dérives du poème”, this article offers a critical analysis of the conception of language underpinning the investment of the poetic act according to Bachelard. Published in Critique de la raison poétique in 1978 and typifying a 1980s critical approach, Esteban’s essay shows how Bachelard maintains and upholds the primacy of philosophy over poetics while at the same time claiming to surmount it. Through the prelinguistic union of words and things, and his investment of discourse in the word, Bachelard effectively reinforced the involvement of poetics in metaphysics, whereas his aim had been to disassociate the one from the other. In demonstrating the invalidity of conceiving the word as a category and model of speech – a move which leads, in Bachelard’s conception, to the annihilation of the subject’s empirical activity in language, to the advantage of Being – Claude Esteban highlights the necessity of interaction between poetics and linguistics. His questioning of those linguistic categories taken for granted by Bachelard aims in particular at the disassociation of poetics from myth, and at a corresponding move towards anthropology. This in turn allows us to reflect on the historic continuity of literary works and their capacity to shift social values.
Keywords: Bachelard; Esteban; word; poetics; myth; philosophy